miR-34a Regulates the Activity of HIF-1a and P53 Signaling Pathways by Promoting GLUT1 in Genetically Improved Farmed Tilapia (GIFT, Oreochromis niloticus) Under Hypoxia Stress - Qiang, Jun; Zhu, Xiao-Wen; He, Jie; Tao, Yi-Fan; Bao, Jin-Wen; Zhu, Jun-Hao; Xu, Pao (Frontiers in Physiology, 2020)
In fish under hypoxia stress, homeostasis can become imbalanced, leading to tissue and organ damage and decreased survival. Therefore, it is useful to explore the molecular and physiological regulation mechanisms that function in fish under hypoxia stress. The microRNA miR-34a is involved in fat and glycogen metabolism, and in apoptosis. In this study, we first verified that GLUT1, the gene encoding glucose transporter 1, is a potential target gene of miR-34a in genetically improved farmed tilapia (GIFT, Oreochromis niloticus) by dual luciferase reporter assays. Then, we clarified the regulatory relationship between miR-34a and GLUT1 by qRT-PCR analyses. We analyzed the regulatory effects of knockdown or promotion of GLUT1 expression in vitro and in vivo in GIFT under hypoxia stress. The results confirm that GLUT1 is a target gene of miR-34a in GIFT. Down-regulation of miR-34a significantly promoted GLUT1 expression. Knockdown of GLUT1 reduced the glycogen content in GIFT liver cells, inhibited HIF-1a gene expression, up-regulated the expression of genes involved in P53 signaling pathways (P53 and CASPASE-3 genes), and accelerated hepatocyte apoptosis under hypoxia stress. Compared with the control group, the group injected in the tail vein with miR-34a antagomir showed up-regulated expression of GLUT1 in the liver, increased liver glycogen content at 96 h of hypoxia stress, down-regulated expression of P53 and CASPASE-3, and decreased serum aspartate aminotransferase and alanine aminotransferase enzyme activities. Our results provide information about the molecular regulation mechanism of miRNAs and their target genes in fish during the response to hypoxia stress.